Evaluation of code compliant/non-compliant ECC-RC IMRF structures. (August 2021) - Khan, Fasih Ahmed; Khan, Sajjad Wali; Rashid, Muhammad; Rizwan, Muhammad; Fahim, Muhammad; Shahzada, Khan; Ahmad, Naveed; Badrashi, Yasir Irfan; Qazi, Samiullah; Said, Imad
Abstract: This paper presents the first-of-its-kind shake table testing and detailed investigation, carried out on one-third reduced-scale Engineered Cementitious Composite-Reinforced Concrete (ECC-RC) hybrid moment-resisting frame structures. The experimental models included a code-compliant model conforming to the seismic building codes and a non-compliant model. The non-compliant model incorporated the deviation of construction practices from the design by using low strength concrete, lacking ties in joints, practicing of 90° hooks, reduction in longitudinal reinforcement ratio, and larger spacing of ties. For structural seismic performance evaluation, the natural acceleration time history of the 1994 Northridge was linearly scaled and applied unidirectionally to both the models through a Shake Table. Seismic response curves were developed by correlating roof displacement demand with the peak sustained acceleration of base motions. The structural natural frequencies and damping ratios were calculated based on free vibration tests. The structural overstrength, displacement ductility ratio, and response modification factor R were also computed. The experimental models with ECC-RC beam-column connections demonstrated the capability to sustain significant lateral displacements at roof-level without jeopardizing the global stability of the structures. The seismic behavior of ECC-RC structural systems shows good promise for potential use in situations where quality assurance on construction sites is not ensured.